Workplace Bullying among Offshore Workers of an Oil and Gas Company - Kamto, Kamto; Nasri, Sjahrul Meizar; Erwandi, Dadan; Lestari, Fatma; Kadir, Abdul (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Workplace bullying is now a psychosocial hazard that has led to deterioration in the productivity of workers, which ultimately leads to the decline in the performance of organizations. This study aimed at examining the correlation between bullying, psychological distress, and satisfaction in life. Respondents involved are offshore workers of an oil and gas company (N = 206) from various entities. Additionally, the respondents were divided into permanent and contract workers, as well as staff and non-staff members recruited using the snowball sampling method. Statistical analysis was performed using the Spearman correlation test with the SPSS software. The results showed a significant association between bullying and psychological distress (r permanent=0.705, r contract=0.548, r staff=0.656, and r non-staff=0.513, p=0.01) and satisfaction with life (r permanent=-0.213, r contract=-0.151, r staff=-0.330, and r non-staff=-0.149, p=0.05). This indicated that permanent workers and staff positions have a higher level of psychological distress than contract workers and non-staff members. However, they also have a higher level of life satisfaction. Therefore, although the stress levels are higher among permanent and staff workers, a mediating factor makes their satisfaction remain higher.